Commencement of systemic corticosteroids in emergency Department versus in ward in management of acute adult asthma requiring hospitalization: a retrospective cohort study (Bangladesh Journal of Medical Science, 2016)
Introduction: Systemic corticosteroids are commonly used in management of acute asthma, sometimes started before admission in emergency department, sometimes in ward after admission. This study is to determine whether commencing systemic corticosteroids in emergency department compared to in ward for managing acute adult asthma requiring hospitalization can improve the outcome: shorter length of hospital stay.Methods: A retrospective cohort study was conducted in an emergency department in Hong Kong. Adults aged 18 to 65 years-old who presented to the emergency department with acute asthma and subsequently hospitalized with use of systemic corticosteroids were recruited and divided into two groups: a group with commencement of systemic corticosteroids in emergency department (Group A, n=139) and the other group with commencement of systemic corticosteroids in ward (Group B, n=209). The outcome measurement was length of hospital stay.Results: A total of 348 subjects were recruited in final analyses. We used Mann-Whitney U test to test the difference in ranking of length of hospital stay (days) between these two groups. The mean rank of length of hospital stay in Group A was 159, and that in Group B was 185 (p=0.014). The difference was statistically significant with commencement of systemic corticosteroids in emergency department resulting in higher ranking-shorter length of hospital stay.Conclusion: It may be possible to result in earlier discharge in acute adult asthma requiring hospitalization when systemic corticosteroids is started before admission in emergency department, instead of in ward after admission.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.608-614